Perfect plasticity of metals under simple shear: geometrical approach - Beygelzimer, Y.; Lavrinenko, N. (Физика и техника высоких давлений, 2012)
A mechanism of perfect plasticity is suggested that implies the phenomenon under study to be of ctitical nature. We consider that it is related to percolation transition in the net of grain boundaries and with nonlocal intraction of fragments uniquely under simple shear. Our point of view is substantiated by general reasoning, mainly of geometrical character, and also by employing computational modeling and well-known experimental results. Предложен механизм идеальной пластичности при простом сдвиге при низких гомологических температурах, согласно которому это явление имеет критическую природу, связанную с перколяционным переходом в сети границ зерен и нелокальным взаимодействием фрагментов именно при простом сдвиге. Точка зрения авторов обоснована довольно общими рассуждениями (в основном геометрического характера) с привлечением с этой целью результатов численного моделирования и известных экспериментальных данных. Запропоновано механізм ідеальної пластичності при простому зсуві при низьких гомологічних температурах, згідно з яким це явище має критичну природу, обумовлену перколяційним переходом у сітці границь зерен і нелокальною взаємодією фрагментів тільки при простому зсуві. Точку зору авторів обґрунтовано загальними міркуваннями з урахуванням результатів чисельного моделювання й відомих експериментальних даних.